Evaluation of endoscopic findings for discriminating between early carcinomas and low-grade adenomas in superficial elevated gastric lesions - Nonaka, Takashi; Inamori, Masahiko; Kanoshima, Kenji; Ohkuma, Kanji; Inoh, Yumi; Matsuura, Mizue; Fuyuki, Akiko; Uchiyama, Shiori; Higurashi, Takuma; Ohkubo, Hidenori; Iida, Hiroshi; Endo, Hiroki; et al. (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: This study aimed to determine the useful endoscopic findings in a differential diagnosis between early carcinomas (EC) and low-grade adenomas (LGA) in superficial elevated gastric epithelial neoplasia during conventional endoscopy with white-light imaging (C-WLI). Materials and Methods: We investigated 270 consecutive cases of superficial elevated gastric epithelial neoplasias, which were removed by endoscopic submucosal dissection. The pathological diagnostic criteria were based on the revised Vienna classification: category 4 (mucosal high-grade neoplasia) or 5 (submucosal invasion by carcinoma) lesions were diagnosed as EC, while category 3 (mucosal low-grade neoplasia) lesions were diagnosed as LGA. The association between the postoperative pathological diagnoses (EC or LGA) and the following endoscopic findings: localized site, lesion size, color (reddish or whitish), shape (smooth, petal, or irregular), and presences of depression, erosion, ulceration, or nodularity on the surface, were evaluated. Results: Of 270 epithelial neoplasias, 222 (58 LGA and 164 EC) were retrospectively evaluated. Multiple logistic regression analysis revealed that the lesion size [odds ratio (OR), 1.216; p<0.001) and reddish color (OR, 5.274; p<0.001) were independent findings for EC. Conclusion: The lesion size and reddish color were useful optical findings for discriminating between EC and LGA.